2022
DOI: 10.3389/fmed.2021.713143
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Polymorphisms in Toll-Like Receptor Genes as Biomarkers of the Response to Treatment of Erythema Nodosum Leprosum

Abstract: Erythema nodosum leprosum (ENL) is an inflammatory complication caused by a dysregulated immune response to Mycobacterium leprae. Some Toll-like receptors (TLRs) have been identified as capable of recognizing antigens from M. leprae, triggering a wide antimicrobial and inflammatory response. Genetic polymorphisms in these receptors could influence in the appearance of ENL as well as in its treatment. Thus, the objective of this work was to evaluate the association of genetic variants of TLRs genes with the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…There is one similar case reported in 2009 which indicated that thalidomide did not affect the cell surface expression of TLR4 [ 21 ], a conclusion that was not reached in our study. As immunomodulatory drugs, thalidomide and its derivatives are effective inhibitors of TLR4-induced TNF-α production [ 39 ]. However, the previous literature did not elucidate whether thalidomide inhibits TLR4 expression.…”
Section: Discussionmentioning
confidence: 99%
“…There is one similar case reported in 2009 which indicated that thalidomide did not affect the cell surface expression of TLR4 [ 21 ], a conclusion that was not reached in our study. As immunomodulatory drugs, thalidomide and its derivatives are effective inhibitors of TLR4-induced TNF-α production [ 39 ]. However, the previous literature did not elucidate whether thalidomide inhibits TLR4 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, emerging research highlights the role of the gut-skin axis in the pathogenesis of autoimmune skin disorders such as psoriasis and vitiligo (Navarro-Lopez et al 2019;Thye et al 2022). Dysregulation of the immune system in the gut can trigger inflammatory cascades that contribute to skin inflammation and tissue damage (Yoo et al 2020;Maciel-Fiuza et al 2023). Modulation of the gut microbiota through interventions such as fecal microbiota transplantation (FMT) and dietary modifications has shown promise in attenuating autoimmune skin diseases by restoring immune homeostasis and dampening inflammatory responses (Navarro-Lopez et al 2019;.…”
Section: Gut Connection: Exploring How Skin Microbiome Impacts Gut He...mentioning
confidence: 99%
“…Maintaining a healthy and balanced microbiota is crucial for protecting human health [1]. Disruption of microbiota balance may lead to various inflammatory and infectious diseases [2]. Many factors are strongly associated with the maintenance or disruption of microbiota balance, among which dietary factors play an important role [3].…”
Section: Introductionmentioning
confidence: 99%